2012
DOI: 10.1208/s12249-012-9873-5
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and In Vitro Drug Release Studies of a Natural Polysaccharide Terminalia catappa Gum (Badam Gum)

Abstract: Abstract. The main objective of the present study is the physicochemical characterization of naturally available Terminalia catappa gum (Badam gum [BG]) as a novel pharmaceutical excipient and its suitability in the development of gastroretentive floating drug delivery systems (GRFDDS) to retard the drug for 12 h when the dosage form is exposed to gastrointestinal fluids in the gastric environment. As BG was being explored for the first time for its pharmaceutical application, physicochemical, microbiological,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
14
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(19 citation statements)
references
References 25 publications
3
14
0
Order By: Relevance
“…From the plots, shown in figures 8 and 9 it was concluded that there was a significant effect of concentration of Badam gum and concentration of HPMC K 15 M on bioadhesion strength. However, the effect of the polymer Badam gum was more pronounced than HPMC K4 M on bioadhesion strength since Badam gum has significant sticking property these findings are in agreement with previously reported results by Meka, et al, [23] who found the Badam gum has remarkable swelling and sticking character in gastric pH. [23][24][25][26][27][28][29][30][31][32][33] This developed floating-bioadhesive combination formulation would overcome the drawback of floating and bioadhesive individual system and improving the therapeutic effect of the drug involved.…”
Section: Bioadhesive Strengthsupporting
confidence: 90%
See 2 more Smart Citations
“…From the plots, shown in figures 8 and 9 it was concluded that there was a significant effect of concentration of Badam gum and concentration of HPMC K 15 M on bioadhesion strength. However, the effect of the polymer Badam gum was more pronounced than HPMC K4 M on bioadhesion strength since Badam gum has significant sticking property these findings are in agreement with previously reported results by Meka, et al, [23] who found the Badam gum has remarkable swelling and sticking character in gastric pH. [23][24][25][26][27][28][29][30][31][32][33] This developed floating-bioadhesive combination formulation would overcome the drawback of floating and bioadhesive individual system and improving the therapeutic effect of the drug involved.…”
Section: Bioadhesive Strengthsupporting
confidence: 90%
“…This gel layer governs the drug released from the matrix tablet. The floating tablets containing Badam gum and HPMC K15M with showed constant increased in swelling because Badam gum and HPMC K15M showed higher swelling and can maintain their matrix integrity for more than 8-9 h similar observation are reported by Meka, et al [23] this erosion of polymer dominates over water sorption after 8 h hence the reduction in tablet weight occurs after 9 h because of constant due to constant erosion of matrix. It might be due to increased hydration of the formed gel layer with time resulted in chain disentanglement and dissolution of the gel layer (erosion), thus decreased SI.…”
Section: Swelling Studysupporting
confidence: 77%
See 1 more Smart Citation
“…There are only a few reports of the use of the almond gum in the development of SR formulations. [5,6] A lipophilic polymer gelucire (43/01) is also employed in the formulation of single unit matrix tablets. Gelucires are a family of relatively inexpensive materials, comprising mixtures of mono-, di-, and triglycerides and also poly (ethylene glycol) esters of fatty acid.…”
Section: Introductionmentioning
confidence: 99%
“…It is medically used as a demulcent and for the treatment of asthma and coughing, while it may also be used as a flavoring agent or preservative (3). Mucilage are biopolymers most commonly used as adjuvants in the manufacturing of different pharmaceutical products and include binding, thickening, stabilizing, humidifying (4,5), disintegrating (6), suspending (7), emulsifying (8), and sustaining properties (9), at different proportions in many pharmaceutical dosage forms. Natural mucilage are preferred over semi-synthetic and synthetic materials due to their non-toxic, low cost, free availability, emollient and nonirritating nature (10).…”
Section: Introductionmentioning
confidence: 99%